HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Yuni Isnaini Nurazizah; Agung Nugroho; Nor Eka Noviani (JOURNAL HEALTH AND NUTRITIONS, 2022)
Female adolescents are more prone than male adolescents to suffer from anemia as a result of menstrual cycles and poor dietary habits. Nutritional imbalances such as insufficient macronutrient and micronutrient consumption, as well as the habit of eating high-calorie but low-nutrient foods (foods high in fat, carbohydrates, and sugar) can induce fat storage and interfere with nutrient metabolism, resulting in anemia. The study aims to analyze the correlation between nutritional status and the incidence of anemia in female adolescents at SMA Negeri 1 Way Tenong, West Lampung. This research employed a quantitative method with an analytical survey with a cross-sectional design. The population of the study was 458 female adolescents in grades X, XI, and XII at SMA Negeri 1 Way Tenong, West Lampung. The sample was taken as many as 140 students using a random sampling technique. The data collected were the identity of the respondent obtained through filling out a questionnaire by the respondent, then checking the nutritional status by measuring height and weight, as well as checking the incidence of anemia by measuring hemoglobin levels. Based on statistical tests using the Chi Square test, a p-value of 0.000 (p <0.1) was obtained which implied that there was a correlation between nutritional status and the incidence of anemia in female adolescent at SMA Negeri 1 Way Tenong, West Lampung. Female adlescents should consume an intake that is appropriate for their needs, with balanced nutrition, and take blood-added supplements on a regular basis.Remaja putri berisiko lebih tinggi terkena anemia dibandingkan remaja laki-laki karena remaja putri mengalami siklus menstruasi dan kebiasaan makan yang salah. Ketidakseimbangan nutrisi berupa kurangnya asupan makronutrien maupun mikronutrien, kebiasaan konsumsi makanan tinggi kalori namun rendah nutrisi (tinggi lemak, karbohidrat, dan gula) dapat menyebabkan penumpukkan lemak dan mengganggu metabolisme penyerapan gizi besi yang kemudian akan berakibat mengalami anemia. Tujuan dilakukannya penelitian ini adalah untuk menganalisis hubungan status gizi dengan kejadian anemia pada remaja putri di SMA Negeri 1 Way Tenong, Lampung Barat. Penelitian ini merupakan penelitian kuantitatif yang bersifat survey analitik dengan desain cross sectional. Populasi penelitian yaitu siswa remaja putri kelas X, XI, dan XII di SMA Negeri 1 Way Tenong, Lampung barat sebanyak 458 siswi. Sampel diambil sebanyak 140 siswi dengan menggunakan teknik random sampling. Data yang dikumpulkan yaitu identitas responden yang didapatkan melalui pengisian kuesioner oleh responden, kemudian pemeriksaan status gizi dengan pengukuran tinggi badan dan berat badan, serta pemeriksaan kejadian anemia dengan melakukan pengukuran kadar hemoglobin. Berdasarkan uji statistik menggunakan uji Chi Square didapatkan hasil p-value sebesar 0,000 (p <0,1) yang disimpulkan bahwa terdapat hubungan status gizi dengan kejadian anemia pada remaja putri di SMA Negeri 1 Way Tenong, Lampung Barat. Disarankan kepada siswa untuk mengonsumsi asupan yang sesuai kebutuhan dengan gizi yang seimbang serta rutin mengonsumsi suplemen tambah darah.